Selective Neuromuscular Denervation in Taiwanese Severe SMA Mouse Can Be Reversed by Morpholino Antisense Oligonucleotides - Lin, Te-Lin (PLoS One, 2016)
Spinal muscular atrophy (SMA) is an autosomal recessive motor neuron disease caused by deficiency of the survival of motor neuron (SMN) protein, which leads to synaptic defects and spinal motor neuron death. Neuromuscular junction (NMJ) abnormalities have been found to be involved in SMA pathogenesis in the SMNΔ7 SMA mouse model. However, whether similar NMJ pathological findings present in another commonly used mouse model, the Taiwanese SMA mouse, has not been fully investigated. To examine the NMJs of the Taiwanese severe SMA mouse model (Smn(-/-); SMN2(tg/0)), which is characterized by severe phenotype and death before postnatal day (P) 9, we investigated 25 axial and appendicular muscles from P1 to P9. We labelled the muscles with anti-neurofilament and anti-synaptophysin antibodies for nerve terminals and α-bungarotoxin for acetylcholine receptors (AChRs). We found that severe NMJ denervation (<50% fully innervated endplates) selectively occurred in the flexor digitorum brevis 2 and 3 (FDB-2/3) muscles from P5, and an increased percentage of fully denervated endplates correlated with SMA progression. Furthermore, synaptophysin signals were absent at the endplate compared to control littermate mice, suggesting that vesicle transport might only be affected at the end stage. Subsequently, we treated the Taiwanese severe SMA mice with morpholino (MO) antisense oligonucleotides (80 μg/g) via subcutaneous injection at P0. We found that MO significantly reversed the NMJ denervation in FDB-2/3 muscles and extended the survival of Taiwanese severe SMA mice. We conclude that early NMJ denervation in the FDB-2/3 muscles of Taiwanese severe SMA mice can be reversed by MO treatment. The FDB-2/3 muscles of Taiwanese severe SMA mice provide a very sensitive platform for assessing the effectiveness of drug treatments in SMA preclinical studies.